PRACTICES OF PRIMARY SCHOOL EFL TEACHER CANDIDATES’ SCREENING AND ADMISSION CRITERIA: SHAMBU TEACHERS’ EDUCATION COLLEGE - Ketema Jiregna Geneti; Yemaneberhan Kelemework; Tamiru Olana (JELLT (Journal of English Language and Literature Teaching), 2021)
This study aimed to assess effectiveness of English language teacher candidates’ screening and admission criteria used to admit quality teacher candidates to English language teacher prepartion. An evaluative case study design was employed. Document analysis and semi structured interview methods were used to collect the data. The study employed purposive sampling techniques to review admission guideline document, choose three English language teacher educators, six teacher candidates, college vice Dean and practicum coordinator. The researcher analysed data thematically in relation to the research questions. The findings show that the screening and admission criteria of English language teacher candidates do not consider candidates’ English language background knowledge, proficiency and interest to teach it. The entrance and interview exams also don’t address candidates’ English language knowledge and communication skills. Overall there is no particular attention to assess candidates’ English language competence and interest to teach English language in the process of screening and admission. To alleviate these gaps, English language teacher preparation program needs to assess candidates’ English language background, communication skills and interest teach English as screening and admitting criteria to teacher preparation